Rapid detection of Vibrio parahaemolyticus using magnetic nanobead-based immunoseparation and quantum dot-based immunofluorescence. Issue 61 (1st December 2021) - Zhai, Yue; Meng, Xiangjun; Li, Li; Liu, Yushen; Xu, Kun; Zhao, Chao; Wang, Juan; Song, Xiuling; Li, Juan; Jin, Minghua
Abstract : IMB probe and QD probe were used as separation and fluorescent label to measure the content of V. parahaemolyticus . The detection method with a detection limit of 10 2 cfu mL −1 has been shown to work satisfactorily in real food samples. Abstract : In recent years, the scale of population exposure and food poisoning caused by Vibrio parahaemolyticus ( V. parahaemolyticus ) has shown a significant upward trend, becoming one of the primary food-borne pathogens. Herein, we developed a rapid and sensitive detection of V. parahaemolyticus by integrating the technology of magnetic nanobeads (MBs) based immunoseparation (IMS) with quantum dots (QDs) based immunofluorescence. Firstly, specific rabbit polyclone IgG antibodies (IgG) and chicken egg yolk antibodies (IgY) of V. parahaemolyticus were prepared. Then two sizes of MBs (1 μm; 180 nm) were coupled with IgG to form immuno-MB (IMB) capture probes for evaluating the effect of different sizes on the detection efficiency. For QDs, they were conjugated with IgY to form fluorescent reporting probes. In the process of detection, IMB probes were used to separate V. parahaemolyticus and then these complexes were labeled by QD probes on the principle of double antibody sandwich. The fluorescence intensity of the IMB- V. parahaemolyticus -QD complexes was measured by a fluorescence spectrophotometer. The detection method takes 150 min with a detection limit of 10 2 cfu mL −1 ranging from 10 2 to 10 6 cfu mL −1 and it has been shown to work satisfactorily in real food samples.